2020
DOI: 10.1104/pp.20.00835
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Gene Analogs in the Brassicaceae: Identification, Characterization, Distribution, and Evolution

Abstract: A resource of resistance genes analogs within Brassicaceae species identifies functional resistance genes to improve plant breeding programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 94 publications
2
56
0
Order By: Relevance
“…Here, the content of LysM of RLKs and RLPs is extremely low in the studied species. Similarly, the number of LysM-RLKs and LysM-RLPs is also very low in previous reports across species from the Brassicaceae family [ 60 ]. To date, the highest number (17) of LysM-RLKs have been separately observed in L. japonicas and M. truncatula [ 61 , 62 ], followed by G. max and P. trichocarpa with 12 and 11 genes, respectively [ 63 ], while less than 10 genes have been observed in A. thaliana (5 genes) and O. sativa (6 genes) [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Here, the content of LysM of RLKs and RLPs is extremely low in the studied species. Similarly, the number of LysM-RLKs and LysM-RLPs is also very low in previous reports across species from the Brassicaceae family [ 60 ]. To date, the highest number (17) of LysM-RLKs have been separately observed in L. japonicas and M. truncatula [ 61 , 62 ], followed by G. max and P. trichocarpa with 12 and 11 genes, respectively [ 63 ], while less than 10 genes have been observed in A. thaliana (5 genes) and O. sativa (6 genes) [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, a higher number of LRR-RLKs has also been identified in polyploid T. aestivum and G. max , with 531 and 467 genes, respectively [ 48 , 57 , 58 , 59 ], and allotetraploid B. napus cv. Darmor V4 (596 genes) [ 60 ]. Accordingly, the LRR-RLP number in B. juncea is also higher than in the diploids B. rapa and B. nigra analysed in this study and the plants previously reported, including A. thaliana (57) [ 12 ], O. sativa (90) [ 21 ] and P. trichocarpa (82) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the number of NLR genes found in the B. oleracea reference genome TO1000 varied widely where Yu et al (2014) and Fu et al (2019) identified around 150 NLRs while Bayer et al (2019) and Alamery et al (2018) found more than 400 NLR genes, however in a different B. oleracea reference pan genome and genome respectively. These differences were not due to the genome assemblies, but the NLR prediction methods (Tirnaz et al, 2020). Variations in the numbers of NLR genes predicted can affect comparative and evolutionary studies.…”
Section: Genome-wide Identification Of Nlr Genes In Brassica Speciesmentioning
confidence: 99%
“…Only 13 of these species have published information on their R gene content ( Table 4 ). There are between 87–641 NLRs, 300–1,556 RLKs, and 56–272 RLPs in the genome assemblies [ 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ] ( Table 3 ).…”
Section: Exploring Resistance Genes In Brassica Napus mentioning
confidence: 99%